Structural, morphology and optical properties of nanocrystalline GaN and AlGaN alloys prepared by EDTA complex route. (May 2016) - Kuppulingam, B.; Garni, S.E. Al; Singh, Shubra; Baskar, K.
Graphical abstract: Highlights: Facile synthesis route to prepare AlGaN nanocrystalline. Focus on the surface morphology and luminescence properties of AlGaN alloy. Synthesis of single-phase hexagonal structured nanocrystalline AlGaN with increasing Al concentration. Importance of AlGaN alloys for advanced nano and optoelectronic device applications. Abstract: GaN and AlGaN alloys were prepared by ethylene diamine tetra acetic acid (EDTA) complex route with five different Al molar ratios. The structure, morphology and luminescence properties of GaN and Al x Ga1− x N were investigated by PXRD, SEM, EDX, HRTEM, PL and Raman techniques. The PXRD pattern confirms the formation of hexagonal wurtzite structure of GaN and Al x Ga1− x N alloys. When Al is alloy with GaN hexagonal shaped particles change into agglomerated spherical and plate-like morphology of Al x Ga1− x N as confirmed by SEM analysis. The results also indicate that with increasing Al composition, the morphology of Al x Ga1− x N changes. HRTEM analysis shows that particle size decreases from 24 to 10 nm, with increasing Al concentration. Raman analysis confirms the presence of E2 (high), A1 (TO), E1 (LO) and A1 (LO) phonon frequencies in AlGaN alloy. PL spectra confirms that the energy of the near band edge emission changes from 383 to 337 nm with change in Al concentration in Al x Ga1− x N samples.